Shari‘ah on Trial: Northern Nigeria’s Islamic Revolution By Sarah Eltantawi (Oakland, CA: University of California Press, 2017. 272 pages.) (American Journal of Islam and Society, 2018)
At the turn of the nineteenth century, a movement of religious reform andstate building took place in present-day northern Nigeria, culminating withthe establishment of the Sokoto Caliphate. This movement was as central toWest African history as was the 1789 French revolution to European history.Its leader, the Muslim scholar Uthman Dan Fodio (d. 1817), deservesrecognition as a towering figure of nineteenth-century African Islam. DanFodio’s community (jamā‘a), which included many scholars, toppled thepreexisting Hausa kingdoms, replacing them with emirates ruled by Fulanileaders who all paid allegiance to the Caliph based in Sokoto. At its zenith,the Caliphate, which became the most powerful economic and political entityof West Africa in the nineteenth century, linked over thirty differentemirates and over ten million people ...